What Is in a Name? A Historical Review of Intelligence Test Score Labels. (September 2019) - Woods, Isaac L.; Floyd, Randy G.; Singh, Leah J.; Layton, Haley K.; Norfolk, Philip A.; Farmer, Ryan L.
Labels for scores stemming from intelligence tests have been employed since their inception in the United States. The purpose of this study was to systematically identify and document score labels for IQs used during the past 102 years. Using pairs of reviewers, score labels from 40 tests were reviewed, and 61 unique labels were identified. Comparative analyses by score range and decade were completed. Results indicate a paradigm shift beginning in the 1980s that has slowly resulted in more common, but not universal, use of terminology that focuses on the statistical aspect of scores, rather than employing value-laden and potentially stigmatizing terms. A universal score label system would help to avoid confusion, miscommunication, and biased decision making.